Explicit Spectral Decimation for a Class of Self-Similar Fractals - Sergio A. Hernández; Federico Menéndez-Conde (Abstract and Applied Analysis)
The method of spectral decimation is applied to an infinite collection of self-similar fractals. The sets considered are a generalization of the Sierpinski Gasket to higher dimensions; they belong to the class of nested fractals and are thus very symmetric. An explicit construction is given to obtain formulas for the eigenvalues of the Laplace operator acting on these fractals.